CHARACTERISTIC OF A STUDENT IN EXPERIMENTAL PEDAGOGY BY O. NECHAEV AND G. ROSSOLIMO - Mikhno Oleksandr (Неперервна професійна освіта: теорія та практика)
In the article, based on the analysis of the works of scientists – the representatives of experimental pedagogy Olexandr Nechaev (1870–1947) and Grigory Rossolimo (1860–1928), their contribution to the development of the problem of the pupil’s profile is highlighted. It has been proved that both scientists paid special attention to this issue, developing it in the following aspects: substantiation of the necessity of studying a pupil by the teacher and improvement of psychological knowledge of the teacher (O. Nechaev); creation of plans for studying the pupil in the form of special questionnaires with detailed recommendations on their use (O. Nechaev, G. Rossolimo), filling out the results of studying the pupil in the form of «psychological profile», which was a graphic representation of the profile (G. Rossolimo). It has been substantiated that, developing a problem of the pupil’s profile, O. Nechaev proceeded from the need to take into account the individual abilities and inclinations of the pupil in the educational process, which could be effectively carried out on the basis of studying the pupil with the subsequent compilation of the pupil’s profile. It has been well-reasoned that relations between scientists were significant in the development of scientific ideas: G. Rossolimo linked the emergence of his method of «psychological profile» directly with the ideas of O. Nechaev. It has been emphasized that the psychological characteristics of various types given by Rossolimo were his contribution to the typology of childhood, along with the typology of P. Lesgaft. These typologies are a significant help to the teacher in the process of learning the pupil and compilation of his profile. It has been emphasized that experimental pedagogy is a scientific phenomenon, the name of which reflects the main method of obtaining empirical knowledge — an experiment that was supposed to guarantee the objectivity of the data obtained, bringing pedagogy to the level of exact sciences; the concept of «experimental pedagogy» is established within the limits of historical–pedagogical discourse as a definition of the scientific phenomenon, characteristic only for the beginning of the XX century.